Deforestation and its effect on livelihood patterns of forest fringe communities in the Asunafo North Municipality - Sadik Mohammed, Abubakari (2015)
A thesis submitted to the school of graduate studies, Kwame Nkrumah University of Science and Technology, in partial fulfillment of the requirements for the award of MASTER OF SCIENCE IN DEVELOPMENT POLICY AND PLANNING. 2014